DIGITALISASI USAHA JASA BOGA LOKAL: PELATIHAN PENGGUNAAN APLIKASI PEMESANAN CATERING BERBASIS ANDROID BAGI UMKM - Muhammad Thaherudin; Koko Setianto; Sakha Muhamad Azis; Muhamad Irfan; Mahesa, (PEMTEKDIKMAS (PENGABDIAN EKONOMI MULTIDISIPLIN TEKNOLOGI PENDIDIKAN UNTUK MASYARAKAT), 2024)
Catering services (food service business) represent significant segment of food industry and service economy in Indonesia. However, most local catering businesses operate using manual systems resulting in operational inefficiencies, limited market reach, and reduced competitiveness. This Community Service Program (PKM) aimed to enhance digitalization capacity of SoesSri Catering through training and implementation of CateringHub mobile application for order booking, menu management, and customer communication. Program involved: (1) needs assessment; (2) Android application development; (3) hands-on training program; and (4) implementation monitoring. CateringHub application features include: digital menu catalogue with pricing, online order booking with delivery scheduling, customer database management, payment integration, and simple business analytics. Participants included 1 owner and 4 staff members. Results after 6 weeks showed: order volume increased 41%, average order value increased 28%, customer database grew from 35 to 128 customers (+266%), customer repeat rate improved from 18% to 48% (+167%), and operational efficiency increased 35%. Training satisfaction reached 88% with 94% competency achievement.